Visual working memory representations guide the detection of emotional faces: An ERP study. (February 2016) - Fan, Lingxia; Ding, Cody; Guo, Renlu; Xu, Mengsi; Diao, Liuting; Yang, Dong
Highlights: An anger superiority effect was confirmed. Visual working memory content influenced attentional selection of emotional faces. Representation in visual working memory could not eliminate anger superiority effect. Abstract: We investigated the correlates of the influences exerted by visual working memory (VWM) on attentional selection of emotional faces using electrophysiological method. Participants performed a search task to detect happy or angry faces among groups of neutral faces while simultaneously keeping in VWM a colour cue presented initially. A visual working memory test was required at last to ensure that the cue had been maintained in VWM. Happy faces elicited a larger amplitude N2pc ERP component when VWM features matched the target face (valid condition) and a smaller amplitude when VWM features matched a distractor face (invalid condition), compared with the neutral condition (wherein VWM features did not match any face in the search array). Additionally, angry faces elicited a greater N2pc amplitude in valid trials than in neutral and invalid trials. Although VWM could guide the attentional deployment of angry and happy faces, the guidance was subject to an anger superiority effect.